2021
DOI: 10.1021/acs.inorgchem.1c02363
|View full text |Cite
|
Sign up to set email alerts
|

A Microporous MOF Constructed by Cross-Linking Helical Chains for Efficient Purification of Natural Gas and Ethylene

Abstract: Natural gas (NG) and ethylene (C2H4) are two raw materials of significant value for manufacturing versatile fine chemicals and/or polymers, and thus the development of solid adsorbing agents such as metal–organic frameworks (MOFs) applied to their depuration is very crucial but remains highly challenging. In this research, we designed and synthesized a ligand containing mixed N and O coordination donors, which was solvothermally assembled with Cu­(II) ions to generate a microporous MOF. X-ray crystallography r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 64 publications
0
9
1
Order By: Relevance
“…The C 2 H 2 uptake of UPC-22 under 1 bar is 46.8 cm 3 g −1 at 273 K and 37.4 cm 3 g −1 at 298 K. For C 2 H 4 and C 2 H 6 , the maximum adsorption capacities are relatively small, only 29.2 and 28.6 cm 3 g −1 at 273 K and 24.2 and 23.4 cm 3 g −1 at 298 K, respectively. The large adsorption capacity of C 2 H 2 with the uptake ratio of C 2 H 2 /C 2 H 4 is 1.55 at 298 K, which is greater than the reported values for the MOF-74 series (1.21-1.36), 34 ZJNU-115 (1.26), 31 ZJNU-119 (1.33), 35 and ZJNU-7 (1.4). 15 The great differences in the adsorption capacity between C 2 H 2 , C 2 H 4 , and C 2 H 6 in UPC-22 revealed the large potential for one-step purification of C 2 H 4 and C 2 H 6 .…”
Section: Permanent Porositycontrasting
confidence: 63%
“…The C 2 H 2 uptake of UPC-22 under 1 bar is 46.8 cm 3 g −1 at 273 K and 37.4 cm 3 g −1 at 298 K. For C 2 H 4 and C 2 H 6 , the maximum adsorption capacities are relatively small, only 29.2 and 28.6 cm 3 g −1 at 273 K and 24.2 and 23.4 cm 3 g −1 at 298 K, respectively. The large adsorption capacity of C 2 H 2 with the uptake ratio of C 2 H 2 /C 2 H 4 is 1.55 at 298 K, which is greater than the reported values for the MOF-74 series (1.21-1.36), 34 ZJNU-115 (1.26), 31 ZJNU-119 (1.33), 35 and ZJNU-7 (1.4). 15 The great differences in the adsorption capacity between C 2 H 2 , C 2 H 4 , and C 2 H 6 in UPC-22 revealed the large potential for one-step purification of C 2 H 4 and C 2 H 6 .…”
Section: Permanent Porositycontrasting
confidence: 63%
“…Nonthermal-driven separation based on the pressure-swing adsorption of porous materials, taking on low-energy investment, high efficiency, a greener productive procedure, and other various preponderances, has become a promising alternative expected to replace the traditional separation technologies . Although lots of versatile types of porous solid adsorptive materials, such as zeolites, alumina, and carbon-based materials, have been developed for the adsorption and separation of light hydrocarbons, they still are incapable of satisfying the separation requirements of industrial demand because of their puny separation selectivity, poor adsorption capacity, and difficult regeneration. , Metal–organic frameworks (MOFs), as one kind of the most sought-after porous materials in recent decades, have been extensively investigated in the territories of gas storage and/or separation and benefit from their excellent surface areas, high pore volumes, structural diversity, tailorable pore sizes, and tunable functionalities. Up to now, a certain number of MOFs as attractive adsorbents have been confirmed that can be used to effectively separate C 2 H 2 /C 2 H 4 mixtures, and research on them is still in the ascendant. By virtue of a scrupulous survey of reported MOF materials with excellent C 2 H 4 purification performances from C 2 H 2 /C 2 H 4 mixtures, we can concisely summarize a number of appealing features that they possess. (1) Pore sizes can be carefully controlled to fit the dynamic diameter of the target molecule, so as to repel or reduce the adsorption of an improper molecule, and the anticipative molecular sieving effect can be achieved effectively .…”
Section: Introductionmentioning
confidence: 99%
“…At a pressure of 1 bar, the adsorption selectivity is 13.0 at 296 K and 11.9 at 273 K for a 1:99 C 2 H 2 /C 2 H 4 mixture. The values surpass those of some recognized MOFs such as Dy-MOF (1.1), ZJNU-14 (1.59), FeMOF-74 (2.08), Cu­(TIA) (2.09), NOTT-300 (2.17), dia-[Sc­(Hpzc)­(pzc)] (3.1), ZJNU-119 (3.5), and NUC-19 (4.0) . When the molar ratio of C 2 H 2 varies from 0.01 to 0.99, the C 2 H 2 /C 2 H 4 selectivity values fall in the range of 13–1.1 at 298 K and 1 bar.…”
Section: Resultsmentioning
confidence: 88%